THE EFFECTS OF SEED PRIMING, PLANTING DATE AND DENSITY ON SILAGE YIELD OF CORN (ZEA MAYS L.) IN SUMMER DELAY SOWING - alipour-abookheili, farshid; mobasser, hamid-reza; siavoshi, morteza (Journal of Agricultural Sciences (Belgrade), 2019)
To determine the effects of seed priming, date and density of planting on silage yield of Corn (Ks.c704 cultivar) in summer delay planting, an experiment was carried out as split-split plot in randomization complete block design with four replications in 2015 and 2016. Treatments were examined in two planting dates (July 27 and August 13) as main plots, two planting densities (7 and 9 plant per m2) as sub plots and four levels of seed priming (without priming, distilled water, 0.5% KNO3 and 10% PEG(8000)) as sub-sub plots. The results showed that the speed and percentage of seedling emergence at the first year is more than second year. Seed priming with distilled water method decreased the number of day from planting date until 8 and 12 leaves stages. The silage yield decreased (26.69%) by the late planting (13 August), but the speed of seedling emergence increased. The planting density (9 plant/m2) yielded the highest percentage of Lignin, the speed of seedling emergence, plant height and silage yield. The highest ratio of the ear-fresh weight to total silage weight was obtained by late planting date (13 August) and seed priming with PEG method. The maximum value of the silage yield (45566.41 kg/ha) was produced by early planting date (27 July) and more planting density (9 plant/m2). Thus, to increase seedling emergence speed and maximum silage yield, early planting date (27 July), more planting density (9 plant/m2) and seed priming by distilled water method are recommended.